Distributed storage causal consistency model with trusted constraint - Junfeng TIAN; Juntao ZHANG; Yanbiao WANG (Tongxin xuebao)
At present, there are few mature solutions to consider security risks in the research field of distributed storage causal consistency.On the basis of hybrid logic clock and HashGraph, combined with trusted cloud alliance technology in trusted cloud platform, a distributed storage causal consistency model (CCT model) with trust constraints was proposed.The CCT model designed identity authentication and consistent data trust verification mechanism on the client side and the server side respectively, and imposed security constraints on the process of data synchronization between data replicas in the cloud storage cluster.Through the simulation experiment, CCT model can identify and verify the identity signature forgery, illegal third party and other security risks in the client and server, and provide the trusted constraint for the system on the premise of causing small performance cost.